P4-S3.03 Characterisation of Ureaplasma parvum from symptomatic and asymptomatic men attending a family practice in Pretoria, South Africa. (10th July 2011) - Kock, M; Maningi, N; Adam, A; Hoosen, A
Abstract : Background: The genus Ureaplasma colonises human mucosal surfaces such as urogenital tract of men and women. In men it has been implicated in the aetiology of non-gonococcal urethritis and infertility. Although its pathogenesis is not yet fully understood, it has been suggested that certain serotypes are associated with disease. This study undertook to detect genital Ureaplasma spp. and to characterise Ureaplasma parvum in men with and without urogenital symptoms. Methods: Two hundred first void urine specimens were collected from symptomatic (100) and asymptomatic (100) men attending a private clinic. All specimens were cultured in U9 broth and subcultured on A2 agar medium for confirmation. All isolates were tested for susceptibility using the Mycofast Evolution 3 kit. DNA was extracted from all specimens and amplified using a multiplex TaqMan polymerase chain reaction assay targeting the multiple-banded antigen gene for the detection and serotyping of U parvum . Ureaplasma urealyticum was detected by a commercial real-time PCR kit. Results: Cultures were positive in 16/100 symptomatic and 12/100 asymptomatic men (p=NS). All isolates were susceptible to doxycycline, pristimycin, roxycycline and azithromycin. One Ureaplasma spp. from an asymptomatic male was resistant to ciprofloxacin and josamycin and intermediately resistant to ofloxacin and another was resistant to ofloxacin. An isolate from a symptomatic man was resistant to ciprofloxacin. There was no significant difference (p=0.16) between the U parvum isolated from symptomatic (11/100) and asymptomatic (18/100) men as well as for U urealyticum from symptomatic 16/100 and asymptomatic 15/100 men (p=0.86). Four men (two from each group) were colonised by both Ureaplasma spp. . The predominant serotype was six, followed by types 1, 14 and 3 with no significant difference between symptomatic and asymptomatic men (p=0.309). Conclusions: There is no data of circulating U parvum serotypes from South Africa. The prevalence rate was low and no significant differences were found between symptomatic and asymptomatic men for both Ureaplasma spp. . Serotype 6 was the most common type compared to reports from developed countries which suggests type 3 as being the most common. Macrolides and tetracyclines remain effective drugs for treatment of the Ureaplasma infections. Molecular techniques are valuable identification and characterisation of this fastidious group of bacteria.